Identifying spatial movements and residency of pelagic thresher sharks (Alopias pelagicus) using satellite and passive acoustic telemetry to inform local conservation in central Indonesia - Shidqi, Rafid A.; Erdmann, Mark V.; Setyawan, Edy; Lezama-Ochoa, Nerea; Sari, Dewi R.; Sianipar, Abraham B.; Stewart, Joshua D.; Croll, Donald A. (Frontiers in Fish Science, 2024)
The pelagic thresher shark (Alopias pelagicus) is globally endangered, threatened by bycatch, and targeted in industrial and artisanal fisheries in Indonesia. However, a lack of information about their ecology, particularly movement and habitat use, hinders the development of science-based conservation measures to protect the species. Here, we report our research, which is the first to use a combination of satellite and passive acoustic telemetry to investigate the movement and residency of the pelagic thresher shark within Indonesia's waters, especially in areas impacted by local fisheries. A total of 24 sharks were tagged with archival satellite tags (n = 9), internal acoustic tags (n = 10), and both tags (n = 5) in Selat Pantar Marine Protected Area (MPA). The tagged sharks, dominated by females (71%) ranged in size from 125–180 cm FL (mean ± SD: 161 ± 13). Seven of the fifteen acoustically tagged sharks were detected by the receivers, while twelve of the fourteen satellite tags reported data. The satellite tags stayed attached for 81–181 days, and the acoustic tag detection periods ranged from 44–175 days. Horizontally, we found the satellite-tagged sharks moved broadly, mainly offshore, approximately 90 km from tagging locations. They moved to areas between Banda, Flores, and Savu Sea regions, where unregulated and unreported longline and gillnet fisheries are known to operate. Meanwhile, the acoustically tagged sharks showed distinct diel patterns around the Selat Pantar MPA's coastal waters, indicating potential philopatric behavior. Vertically, the sharks spent significantly (p < 0.001) more time in deeper water during the day and moved to shallower water at night. The deepest dive recorded was 1,889.5 m, which is the deepest ever recorded from the species. Our results suggest that area-based protection can be an effective nearshore conservation tool as individuals appear to remain in relatively restricted areas within Selat Pantar MPA for extended periods. However, fisheries regulation aimed at restricting illegal longline and gillnet fishing is also necessary to protect sharks when they move offshore. Our findings have been communicated to the relevant governments, resulting in increased political will and new legislation to protect them within the Selat Pantar MPA and connected waters of East Nusa Tenggara.